Implementasi Metode Talaqqi Dalam Pembelajaran Tahsinul Qur’an Di Pondok Pesantren Ahmad Dahlan Candipuro - Hidayat, Rahmat; Luviadi, Ahmad; Eka Putra, Arizal (Universitas Majalengka, 2024)
This study aims to investigate the implementation of the talaqqi method in Tahsinul Qur’an learning at Pondok Pesantren Ahmad Dahlan Candipuro. The talaqqi method is a traditional approach involving direct interaction between teachers and students to improve Qur’anic recitation. This research adopts a qualitative approach with data collection techniques including observation, interviews, and documentation studies. The findings indicate that the implementation of the talaqqi method in the pesantren involves a structured and continuous process, where teachers provide individual attention to each student to improve their recitation and pronunciation. Additionally, the talaqqi method facilitates the formation of close relationships between teachers and students, and encourages the development of Islamic character through positive social interactions within the pesantren environment. The implications of this research contribute to a better understanding of the application of traditional methods in the context of Tahsinul Qur’an learning in modern pesantrens.